Aggression and 5HTT polymorphism in females: Study of synchronized swimming and control groups - Sysoeva, O. V.; Maluchenko, N. V.; Timofeeva, M. A.; Portnova, G. V.; Kulikova, M. A.; Tonevitsky, A. G.; Ivanitsky, A. M. (International Journal of Psychophysiology, 2009)
Aggression is a heterogeneous heritable psychological trait, also influenced by environmental factors. Previous studies, mostly conducted on male population, have found some associations of the aggression with the polymorphisms of genes, regulating the activity of serotonin (5-HT) in the brain. However, psychological as well as biochemical manifestations of the aggression are different in males and females. Our study aimed to investigate the association of 5-HTT gene polymorphism with different facets of aggression (BDHI) in females. Two groups: the synchronized swimming and non-athlete control, — were examined to study the possible modulation effect of sport on the association between 5-HTT gene polymorphism and aggression. It was found that in both groups the low-active 5-HTT polymorphism (SS) was associated with increased scores on Indirect Hostility scale and decreased scores on Negativism scale, compared to LL genotype. No interaction effect between sport and 5-HTT polymorphism was found. The higher percentage of LL-carriers and lower of LS-carriers in the synchronized swimming group compared to the control one was observed. This may be the sign of the importance of LL polymorphism of 5-HTT gene, previously associated with higher resistance to stress factors, for being an athlete, although this result has to be taken cautiously keeping in mind the stratification problem. Synchronized swimmers had lower scores on Assault, Negativism, Irritability and Verbal Hostility compared to age-matched control girls (in general and for each 5-HTT genotype separately), suggesting that they may have more matured emotional system (older control group has also lower scores on these scales).